Merging processes in galaxy clusters - Feretti, L. (Luigina); Gioia, I. M. (Isabella M.); Giovannini, G. (Gabriele) (Astrophysics and space science library, 2002)
Mergers are the mechanisms by which galaxy clusters are assembled through the hierarchical growth of smaller clusters and groups. Major cluster mergers are the most energetic events in the Universe since the Big Bang. Many of the observed properties of clusters depend on the physics of the merging process. These include substructure, shock, intra cluster plasma temperature and entropy structure, mixing of heavy elements within the intra cluster medium, acceleration of high-energy particles, formation of radio halos and the effects on the galaxy radio emission. This book reviews our current understanding of cluster merging from an observational and theoretical perspective, and is appropriate for both graduate students and researchers in the field.